Adopting Kendall’s Tau B Correlation Model to Assess Organisational Conflict and Job Commitment of Olam Flour Mill, Ilorin - Ahmed, Nurudeen Bello Ahmed; Salau, Abdulazeez Alhaji Salau; Adebayo, Titilayo Bamidele Adebayo (African Journal of Stability and Development (AJSD), 2025)
The existence of every organisation is a result of the peace and harmonious working relationship enjoyed by both the staff and management of such companies. Olam Flour Mills Limited is no exception, though the company records some differences emanating from internal wranglings and staff commitment issues. The objective of the study is to investigate the impact of job commitment on organisational conflict in Olam Flour Mills, Ilorin. The study, making use of a finite population of 232 staff members of the company, adopts a survey research design that is cross-sectional in nature. Using Krejcie and Morgan’s table (1970), the study’s sample size was determined to be 148. The study employed a simple random sampling technique because the staff share similar characteristics. The findings were analysed using multiple regression analysis to test the hypothesis. The results indicate that job commitment has a significant impact on organisational conflict, with a value of 0.423 and a significance level of 0.000. The study concludes that job commitment significantly affects organisational conflict. Therefore, management of conflict in Olam Flour Mills Ilorin among staff greatly affects the organisation. The study recommends that organisations should place emphasis on managing conflicts effectively because poor conflict management can have devastating effects on an organisation.